Estudo dos fatores de risco e do impacto da lesão renal no transplante hepático - Narciso, Roberto Camargo [UNIFESP] (2011)
The acute and chronic renal diseases have distinct impacts on the outcome of liver transplantation (LTx). While the acute form determines high mortality soon after the transplantation procedure, most patients will recover to the point of being discharged from hospital. In the chronic form, progressive loss of renal function implies in increased long term mortality and reduced quality of life. We studied the transplants performed between January 2002 and November 2006 in a single center. During this period, 444 LTxs were performed in 395 patients. The common objective was to identify the risk factors involved in the genesis of renal disease after transplantation in both acute and chronic forms, and their impact on patient survival. In the first study, we evaluated the impact of time elapsed between the onset of Acute Kidney Injury (AKI) according to criteria established by AKIN (Acute Kidney Injury Network) and the beginning of recovery of kidney function or initiation of renal replacement therapy (RRT) on the mortality of patients undergoing to LTx. The cumulative incidence of AKI in 48 hours, one week and throughout the hospital stay was 32%, 81% and 93% respectively. RRT was required within one week after LTx in 31 procedures (10%) and other 17 (5%) after this period. The time in days from diagnosis of AKI until RRT initiation or peak of serum creatinine was associated with shorter overall survival, even when adjusted for major confounders (hazard ratio [HR] 1.03, 95% confidence interval [CI] 1.01; 1.05, p=0.002). In general, patients with AKI, lasting a week or more before the start of RRT had a threefold increase on the risk of death (HR 3.02, CI 2.04; 4.46, p<0.001). We conclude that AKI after LTx is frequent and has great impact on patient survival. Delay the beginning of RRT increases mortality in more than 20% per day in this population. In the second study, we analyzed the impact of different conditions pre-liver transplantation and the evolution of renal function in 331 patients undergoing LTx. The average follow up was 2.5 years. Stage 5 Chronic Kidney Disease (CKD) was achieved by 10% of patients, with 8% remaining in RRT program for chronic patients and 2% receiving a kidney after LTx. The presence of renal dysfunction prior to transplantation, liver neoplastic disease, severe liver graft dysfunction and APACHE II score were identified as independent risk factors for the combined outcome death or end-stage CKD. Patients with preoperative estimated glomerular filtration rate (eGFR) lower than 60 ml/min/1.73m² had a fourfold increase in risk of developing stage 5 CKD, after adjustment for sex, diabetes mellitus, APACHE II score, postoperative use of nephrotoxic drugs and severe graft liver failure (HR = 3.95, CI 1.73; 9.01, p = 0.001). Other independent risk factors for stage 5 CKD were preoperative diabetes mellitus, severe liver graft dysfunction. Patients who became dialysis dependent had shorter survival, although this was partially reversed after kidney transplantation. We conclude that low eGFR before LTx is a predictor of chronic renal failure or death. Kidney after liver transplantation should be considered as the treatment modality of choice for those who develop chronic renal failure requiring dialysis after the LTx.